Application of FTIR and LA-ICPMS Spectroscopies as a Possible Approach for Biochemical Analyses of Different Rat Brain Regions - Mohamed H. M. Ali (18140584) (2018)
Fourier Transform Infrared Spectroscopy (FTIR) is a non-destructive analytical technique that has been employed in this research to characterize the biochemical make-up of various rat brain regions. The sensorimotor cortex, caudate putamen, thalamus, and the hippocampus were found to have higher olefinic content—an indicator of a higher degree of unsaturated fatty acids—rich in short-chain fatty acids, and low in ester and lipid contents. While the regions of the corpus callosum, internal, and external capsule were found to contain long-chained and higher-esterified saturated fatty acids. These molecular differences may reflect the roles of the specific regions in information processing and can provide a unique biochemical platform for future studies on the earlier detection of pathology development in the brain, as a consequence of disease or injury. Laser Ablation Inductively Coupled Plasma Mass Spectroscopy (LA-ICP-MS) is another vital analytical technique that was used in this work to analyze the elements’ distribution patterns in various regions of the brain. The complementary data sets allowed the characterization of the brain regions, the chemical dominating groups, and the elemental composition. This set-up may be used for the investigation of changes in the brain caused by diseases and help create a deeper understanding of the interactions between the organic and elemental composition. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app8122436